Magnetic field effects on methane–air combustion and emissions in an optical constant volume combustion chamber - Jhe-Kai Lin; Son Hoang Do; Wei-Cheng Wang; Chun-Hao Chiu; Po-Wei Chen; Thong Duc Hong (Fuel, 2026)

Gut microbiota profiles across intrinsic capacity strata in community-dwelling older adults using full-length 16S rRNA sequencing - Chi-Hsien Huang; I-Cheng Lu; Chi-Wei Lin; Ming-Ta Hsieh; I-Hui Chiang; Po-Hsuan Lai; I-Ting Liu; Jung-Sheng Chen (GeroScience, 2026)

Comparative Online–offline measurement of airborne toxic VOCs for health risk and source identification in an environmental justice community - Hsin-Cheng Hsieh; Yuan-Chang Su; Sheng-Po Chen; Chen-Hsuan Chu; Mei-Hui Tseng; Kuan-Chun Lee; Po-Sheng Tseng; Pei-Hsuan Hsu; Chih-Chung Chang; Chieh-Heng Wang; Jia-Lin Wang (Atmospheric Environment, 2026)

Operational Performance of Aquavoltaics Under Different Stakeholder Cooperation Schemes: Evidence from White Shrimp Aquaculture in Taiwan - Bo-Ying Chen; Po-Lin Huang; Yen-Lung Hou; Farok Afero; Szu-Han Liu; Cheng-Ting Huang (Fishes, 2026)
Aquaculture faces rising climate-change risks, while photovoltaic power generation requires substantial land resources, underscoring the need for multifunctional land use in the energy transition. Aquavoltaics—combining aquaculture with solar power—has emerged, and its success depends on stakeholder cooperation. Using white shrimp aquaculture in Taiwan as a case study, this study examines four cooperation schemes—a sole-investment scheme, a photovoltaic-led leasing scheme, a landowner lease-back scheme, and a separated aquaculture and photovoltaic operation scheme—across six aquavoltaic types. Cost–benefit and data envelopment analyses assess the economic returns and operational efficiency of aquaculture operators and photovoltaic companies under each scheme. The results show that all schemes offer profit potential but differ in efficiency and income distribution. The landowner lease-back scheme is most efficient for aquaculture operators, while photovoltaic companies operate near the efficiency frontier in all schemes. The findings highlight that cooperation design shapes the economic feasibility, efficiency, and livelihood impact of aquavoltaic systems, providing a useful reference for future policy and model design.

Late quaternary eruption history of the Tatun Volcano Group (Taiwan) – new constraints from zircon double-dating and 40Ar/39Ar dating of lava flows in Mt. Shamao - Karl D. Jabagat; Yuan-Hsi Lee; Martin Danišík; Daniel Miggins; Mei-Fei Chu; Yu-Ming Lai; Yun-Chieh Lo; Po-Tsun Lee; Cheng-Horng Lin (Tectonophysics, 2026)

Engineering supersaturation for the recovery of lanthanum as lanthanum phosphate via fluidized-bed crystallization - Po-Lin Liao; Thanh Binh Nguyen; Chiu-Wen Chen; Cheng-Di Dong (Journal of Water Process Engineering, 2026)

Flexible and compressible thermoelectric foam for temperature–pressure dual sensor - Po-Shen Lin; Meng Li; Yong-Qi Chen; Bo-Xuan Hu; Cheng-Liang Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2026)

Coupled oxygen and nitrogen defect sites in Co-N4-coordinated frameworks facilitate stepwise CO2 methanation - Pin-Yu Liu; Sheng-Xiang Chou; Wei-Tse Sun; Hsin-Han Chen; Cheng-Hung Tsai; Yen-Lin Lai; Yu-Cheng Shao; Chi-Liang Chen; Yu-Ching Huang; Yun-Wei Chiang; Bo-Hong Liu; Chia-Hsin Wang; et al. (Chemical Engineering Journal, 2026)

A UAV-based multispectral imaging approach for tea shoots aerial mapping and assessment - Hsin-Cheng Chen; Shiou-Ruei Lin; Po-An Chen; Ta-Te Lin (Precision Agriculture, 2026)

Association between urinary metabolites of 1,3-butadiene and toluene exposure with kidney function indices in Taiwanese school-aged children living near a petrochemical complex - Po-Keng Cheng; Vinoth Kumar Ponnusamy; Wei-Hong Lin; Jeganathan Chinnadurai; Pei-Chien Tsai; Cai-Yu Chen; Wan-Ting Chang; Po-Chin Huang (Environmental Pollution, 2026)

Isomeric halide engineering of self-assembled hole-selective layers for efficient indoor perovskite photovoltaics - Zhong-En Shi; Yi-Ting Hong; Cheng-Chieh Lu; Po-Cheng Shih; Shih-I Lu; Hsiao-Chi Hsieh; Sie-Rong Li; Yu-Che Lin; Zheng-Xuan Cai; Yan-Duo Lin; Chih-Ping Chen (Chemical Engineering Journal, 2026)

Microbial, genetic, and urban drivers of ant invasions - Wei-Jiun Lin; Po-Wei Hsu; Edward L Vargo; Chin-Cheng Scotty Yang (Current Opinion in Insect Science, 2025)

Interplay of plasma-treated BiVO4 photoanode and CoFe metal organic frameworks enabled synergistic photoelectrochemical water splitting - Zhi-Cheng Yan; Min-Ho Lin; Chen-Hao Yeh; Pei-Lun Chen; Jun Song Chen; Po-Hsuan Hsiao; Chia-Yun Chen (Chemical Engineering Journal, 2025)

Protecting Migrant Labor Rights in the Distant-Water Fisheries Sector: A Comparative Analysis of the Legal Framework of Three Major Fishing Nations in Eastern Asia - Wen-Hong Liu; Po-Chih Hung; Peter Vandergeest; Azmath Jaleel; Bruno Ciceri; Chih-Cheng Lin (Reviews in Fisheries Science & Aquaculture, 2025)

Novel synthesis and application of biochar for controlling release and exposure of mercury in the farmland: From human health risk perspective - Nathan Thadeo Yoashi; Che-Jung Hsu; Ying-Lin Wang; Po-Hui Wu; Zheng-Yei Hseu; Ling-Chu Chien; Hsing-Cheng Hsi (Environmental Research, 2025)

Enhancing color conversion of perovskite quantum dot-based micro-light-emitting diodes via electrochemical etching and flow chemistry system - Wen-Tse Huang; Yen-Huei Lin; Po-Yi Tu; Loan Thi Ngo; Wei-Cheng Chen; Kai-Ling Liang; Yen-Hsiang Fang; Chaochin Su; Ru-Shi Liu (Chemical Engineering Journal, 2025)

Synergistic properties of single-component hexagonal iron borate for superior and sustainable photo-Fenton catalysis - Po-Yi Wu; Jing-Cheng Hsu; Tsung-Yueh Lin; Yu-Lun Zhu; Yu-Rong Chang; Pei Yuin Keng (Journal of Environmental Chemical Engineering, 2025)

Impact of Coal-Fired Power Plants on Suspended Sediment Concentrations in Coastal Waters - Zhi-Cheng Huang; Po-Chien Lin; Po-Hsun Lin; Shun-Hsing Chuang (Journal of Marine Science and Engineering, 2025)
Many coastal coal-fired power plants utilize seawater flue gas desulfurization (SWFGD) systems, which may pose risks of heavy metal attachment on suspended sediments. Understanding variations in suspended sediment concentration (SSC) is therefore useful for controlling marine pollution. We studied two power plants as examples of discharging SSC using continuous measurement techniques. Monitoring sites at intake and discharge points and the surrounding coastal areas of the power plants was conducted across seasons. The first case study, Linkou Power Plant, is located in a high-SSC region influenced by monsoon winds and wave activity. Results indicate that SSC levels at all the monitoring sites are correlated with environmental factors of wind and wave conditions, with strong positive correlations observed between the intake and discharge points. In contrast, the Dalin Power Plant is located within an international harbor, where the SSC levels are generally low; however, sudden increases in SSC are observed at the intake point due to disturbances from vessel activities. These sudden increases are not evident at the discharge point, suggesting a sink of SSC may occur within the system. These results demonstrate that the two studied power plants have limited effects on the increase in SSC; the SSC in the discharge point is mainly related to the SSC input at the intake point. Effective management of SSC at the intake may help mitigate coastal pollution caused by SSC discharge and reduce the risk of harmful substances adhering to suspended solids in the discharging wastewater.

Determination of pullout capacity for an inclined single-plate helical pile under combined loading in clay - Fei Liu; Po Cheng; Hongnan Lin; Jiangtao Yi; Yu Peng; Jun Hu; Ya-pei Chu (Marine Georesources & Geotechnology, 2025)

Safety evaluation of Limosilactobacillus fermentum PS150 for use as a commercial psychobiotic - Li-Hao Cheng; Chien-Chen Wu; Chin-Lin Huang; Yu-Hsuan Wei; Pei-Jun Wen; Shih-Hau Chiu; Chien-Chi Chen; Ching-Ting Lin; Po-Lin Liao (Food and Chemical Toxicology, 2025)

Investigation of the abasic sites induced by hydrogen peroxide and methyl methanesulfonate in calf thymus DNA and BEAS-2B cells - Dat Thanh Dinh; Gilang Putra Bahari; Qi Xu; Cheng-Hao Wei; Dar-Ren Chen; Wei-Chung Hsieh; Po-Hsiung Lin (Toxicology Letters, 2024)

Gel electrolyte design for nonflammable lithium-ion batteries with high-rate and high-voltage characteristics - Po-Wei Huang; Qin-Cheng Zhang; Ming-Yuan Hung; Yan-Cheng Lin; Hong-Kang Tian; Yuh-Lang Lee; Jeng-Shiung Jan; Hsisheng Teng (Chemical Engineering Journal, 2024)

Advances in perfluoro-alkylated compounds (PFAS) detection in seafood and marine environments: A comprehensive review on analytical techniques and global regulations - Prasath Ramasamy Chandrasekaran; Jeganathan Chinnadurai; Yee Cheng Lim; Chiu-Wen Chen; Pei-Chien Tsai; Po-Chin Huang; Mohsen Gavahian; Gangadhar Andaluri; Cheng-Di Dong; Yuan-Chung Lin; Vinoth Kumar Ponnusamy (Environmental Geochemistry and Health, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Improvement of the Diagnostic Method for the Detection of Parasite Eggs Using the Formalin Ethyl Acetate Concentration Technique - Jia-Hung Liou; Te-Ling Lu; Hui-Fen Cheng; Long-Wei Lin; Po-Cheng Kung; Hong-Jing Chuang; Te-Hsiu Lee; Chee-Hong Chan; Te-Jung Lu (Acta Parasitologica, 2024)

Predicting ischemic stroke patients’ prognosis changes using machine learning in a nationwide stroke registry - Ching-Heng Lin; Yi-An Chen; Jiann-Shing Jeng; Yu Sun; Cheng-Yu Wei; Po-Yen Yeh; Wei-Lun Chang; Yang C. Fann; Kai-Cheng Hsu; Jiunn-Tay Lee (Medical & Biological Engineering & Computing, 2024)
Accurately predicting the prognosis of ischemic stroke patients after discharge is crucial for physicians to plan for long-term health care. Although previous studies have demonstrated that machine learning (ML) shows reasonably accurate stroke outcome predictions with limited datasets, to identify specific clinical features associated with prognosis changes after stroke that could aid physicians and patients in devising improved recovery care plans have been challenging. This study aimed to overcome these gaps by utilizing a large national stroke registry database to assess various prediction models that estimate how patients’ prognosis changes over time with associated clinical factors. To properly evaluate the best predictive approaches currently available and avoid prejudice, this study employed three different prognosis prediction models including a statistical logistic regression model, commonly used clinical-based scores, and a latest high-performance ML-based XGBoost model. The study revealed that the XGBoost model outperformed other two traditional models, achieving an AUROC of 0.929 in predicting the prognosis changes of stroke patients followed for 3 months. In addition, the XGBoost model maintained remarkably high precision even when using only selected 20 most relevant clinical features compared to full clinical datasets used in the study. These selected features closely correlated with significant changes in clinical outcomes for stroke patients and showed to be effective for predicting prognosis changes after discharge, allowing physicians to make optimal decisions regarding their patients’ recovery. Graphical Abstract

The economic feasibility of aquavoltaics in Taiwan - A case study of whiteleg shrimp (Litopenaeus vannamei) culture - Bo-Ying Chen; Po-Lin Huang; Yen-Lung Hou; Hsun-Yu Lan; Cheng-Ting Huang; Fan-Hua Nan (Aquaculture, 2024)

Ozone containment through selective mitigation measures on precursors of volatile organic compounds - Sheng-Po Chen; Wen-Tzu Liu; Fang-Yi Cheng; Chieh-Heng Wang; Shih-Ming Huang; Jia-Lin Wang (Science of The Total Environment, 2024)

The Bioeconomic Analysis of Hybrid Giant Grouper (Epinephelus fuscoguttatus × Epinephelus lanceolatus) and Green Grouper (Epinephelus malabaricus): A Case Study in Taiwan - Po-Lin Huang; Farok Afero; Yao Chang; Bo-Ying Chen; Hsun-Yu Lan; Yen-Lung Hou; Cheng-Ting Huang (Fishes, 2023)
Grouper aquaculture is a rapidly growing and dynamic industry within the Taiwan aquaculture sector that serves as an important source of income generation. Farming fishes at a better location (FFABL) is a promising production strategy. This study evaluated the production and economic performance of grouper farming in Taiwan. This investigation employed two steps: (1) a cost–benefit analysis to determine the main component affecting profitability; and (2) multivariate statistics to clarify the relationship between biological and economic factors. The findings suggest that the best choice of species is hybrid giant grouper that generates and highlights a positive income, viable benefit–cost ratio and profit rate. The study found the feed management of hybrid giant groupers requires more consideration due to its low feed conversion ratio. The producers need to replace trash fish in commercial feed during the production cycle to ensure better feed management. Finally, this paper argues that feed is the main constraint for grouper farming, which is sensitive to any change in feed productivity, and this constraint must be solved to sustain the grouper industry in Taiwan.

Inhibition of continuous cropping obstacle of celery by chemically modified biochar: An efficient approach to decrease bioavailability of phenolic allelochemicals - Chia-Chia Lin; Yu-Ting Liu; Po-Hsiang Chang; Yi-Cheng Hsieh; Yu-Min Tzou (Journal of Environmental Management, 2023)

Quantifying the potential effects of air pollution reduction on population health and health expenditure in Taiwan - Yi-Hsuan Roger Chen; Wan-Chen Lee; Bo-Chen Liu; Po-Chieh Yang; Chi-Chang Ho; Jing-Shiang Hwang; Tzu-Hsuan Huang; Hsien-Ho Lin; Wei-Cheng Lo (Environmental Pollution, 2023)

Nanoscale photocatalytic hydrogen production system mitigates inflammation by harnessing glycolysis waste - Cheng-Yu Wu; Cam-Hoa Mac; Tung-Han Yang; Khanh Nguyen; Shih-Kai Lo; Yen Chang; Po-Liang Lai; Hsing-Wen Sung; Yu-Jung Lin (Chemical Engineering Journal, 2023)

Effects of ammonia on combustion of coal in stoichiometric premixed methane–air flames - Yueh-Heng Li; Bo-Cheng Chuang; Po-Hung Lin; Janusz Lasek (Fuel, 2023)

Cost-effective and accurate monitoring of flowering across multiple tropical tree species over two years with a time series of high-resolution drone imagery and deep learning - Calvin Ka Fai Lee; Guangqin Song; Helene C. Muller-Landau; Shengbiao Wu; S. Joseph Wright; K.C. Cushman; Raquel Fernandes Araujo; Stephanie Bohlman; Yingyi Zhao; Ziyu Lin; Zounachuan Sun; Peter Chuen Yan Cheng; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Artificial intelligence and visual analytics in geographical space and cyberspace: Research opportunities and challenges - Min Chen; Christophe Claramunt; Arzu Çöltekin; Xintao Liu; Peng Peng; Anthony C. Robinson; Dajiang Wang; Josef Strobl; John P. Wilson; Michael Batty; Mei-Po Kwan; Maryam Lotfian; et al. (Earth-Science Reviews, 2023)

Involvement of microRNA164 in responses to heat stress in Arabidopsis - Wei-An Tsai; Po-Han Sung; Yun-Wei Kuo; Ming-Cheng Chen; Shih-Tong Jeng; Jeng-Shane Lin (Plant Science, 2023)

Effectiveness of Combined Exercise and Physiotherapy Intervention in Improving Functional Activity of Patients with Knee Osteoarthritis in Muslim Pray Movements - Rakhmad Rosadi; Po-Ting Wu; Yu-Lin You; Li-Chieh Kuo; Cheng-Feng Lin (Journal of Medical and Biological Engineering, 2023)

The role of branched alkylthio side chain on dispersion and thermoelectric properties of regioregular polythiophene/carbon nanotubes nanocomposites - Po-Shen Lin; Shin Inagaki; Jia-Hao Liu; Ming-Chou Chen; Tomoya Higashihara; Cheng-Liang Liu (Chemical Engineering Journal, 2023)

Infusing satellite data into aerosol forecast for near real-time episode detection and diagnosis in East Asia - Sheng-Po Chen; Cheng-Hsuan (Sarah) Lu; James E. Davies; Chang-Feng Ou-Yang; Neng-Huei Lin; Amy K. Huff; Bradley R. Pierce; Shobha Kondragunta; Jia-Lin Wang (Science of The Total Environment, 2023)

Intimate interaction of TFSI− anions with MoO3−x oxygen vacancies boost ionic conductivity of cathode-supported solid polymer electrolyte - Rohan Paste; Chintam Hanmandlu; Po-Yu Su; Cheng-Hung Hou; Hsin-An Chen; Chun-Wei Pao; Jing-Jong Shyue; Kuei-Hsien Chen; Heng-Liang Wu; Hong-Cheu Lin; Chih Wei Chu (Chemical Engineering Journal, 2023)

Promoting human rights for Taiwan’s fishermen: Collaboration with the primary source countries of Taiwan’s DWF migrant fishermen - Po-Chih Hung; Hsiao-Chien Lee; Chih-Cheng Lin; Wen-Hong Liu (Frontiers in Marine Science, 2022)
Taiwan is one of the largest distant water fishing (DWF) nations worldwide, and relies largely on the migrant labor to keep costs low. However, this industry has caused Taiwan to be listed in the 2020 “List of Goods Produced by Child Labor or Forced Labor” of the U.S. Department of Labor. In view of this, the Taiwanese government is actively adopting further management measures to supervise the domestic and foreign fishermen agencies. It is because the latter has been involved in many disputes, especially in recruitment, payroll, and labor contracts, which directly or indirectly affect the rights of migrant fishermen. On the other hand, although the C188 Work in Fishing Convention has stregthend the protection of the fishermen’s human rights, it still stays ambiguous in terms of private agency management. That is also why so many disputes have been caused in recent years.This study conducts a comparative analysis of the agency management systems in the primary source countries of Taiwan’s distant water fishing migrant fishermen (that is, Indonesia, the Philippines, and Vietnam), as well as interviews with distant water fishing stakeholders to provide insights on the improvement of agency management and migrant fishermen’s rights in Taiwan. The findings imply that the positive interaction, mutual trust, and understanding of laws and regulations between fishermen’s exporting and importing countries lead to future cross-national collaboration. This study suggests that the Taiwanese government should follow the spirit of the C188 but not be restricted to the Convention texts to amend or formulate regulations and policies of agencies for fully protecting the rights of migrant fishermen.

Mesenchymal Stem Cell Secreted-Extracellular Vesicles are Involved in Chondrocyte Production and Reduce Adipogenesis during Stem Cell Differentiation - Yu-Chen Tsai; Tai-Shan Cheng; Hsiu-Jung Liao; Ming-Hsi Chuang; Hui-Ting Chen; Chun-Hung Chen; Kai-Ling Zhang; Chih-Hung Chang; Po-Cheng Lin; Chi-Ying F. Huang (Tissue Engineering and Regenerative Medicine, 2022)
Background: Extracellular vesicles (EVs) are derived from internal cellular compartments, and have potential as a diagnostic and therapeutic tool in degenerative disease associated with aging. Mesenchymal stem cells (MSCs) have become a promising tool for functional EVs production. This study investigated the efficacy of EVs and its effect on differentiation capacity. Methods: The characteristics of MSCs were evaluated by flow cytometry and stem cell differentiation analysis, and a production mode of functional EVs was scaled from MSCs. The concentration and size of EVs were quantitated by Nanoparticle Tracking Analysis (NTA). Western blot analysis was used to assess the protein expression of exosome-specific markers. The effects of MSC-derived EVs were assessed by chondrogenic and adipogenic differentiation analyses and histological observation. Results: The range of the particle size of adipose-derived stem cells (ADSCs)- and Wharton’s jelly -MSCs-derived EVs were from 130 to 150 nm as measured by NTA, which showed positive expression of exosomal markers. The chondrogenic induction ability was weakened in the absence of EVs in vitro . Interestingly, after EV administration, type II collagen, a major component in the cartilage extracellular matrix, was upregulated compared to the EV-free condition. Moreover, EVs decreased the lipid accumulation rate during adipogenic induction. Conclusion: The results indicated that the production model could facilitate production of effective EVs and further demonstrated the role of MSC-derived EVs in cell differentiation. MSC-derived EVs could be successfully used in cell-free therapy to guide chondrogenic differentiation of ADSC for future clinical applications in cartilage regeneration.

Recent Developments in Additive-Manufactured Intermetallic Compounds for Bio-Implant Applications - Po-Yuan Yeh; Jacob C. Huang; Jason S. C. Jang; Cheng-Tang Pan; Chung-Hwan Chen; Che-Hsin Lin (Journal of Medical and Biological Engineering, 2022)
Purpose This paper reviews the recent developments of two newly developed intermetallic compounds (IMCs) of metallic glasses (MGs) and high-entropy alloys (HEAs) as potential implantable biomaterials. Methods The paper commences by summarizing the fundamental properties of recently developed MGs and high-entropy alloys (HEAs). A systematic review is presented of the recent literature about the use of AM technology in fabricating MG and HEA components for biological implant applications. Results The high strength, low Young’s modulus, and excellent corrosion resistance make these IMCs good candidates as bio-implantable materials. Recent studies have shown that additive manufacturing (AM) techniques provide an advantageous route for the preparation of glassy metallic components due to their intrinsically rapid cooling rates and ability to fabricate parts with virtually no size or complexity constraints. A practical example is conducted by AM producing a porous gradient Ti-based MG spinal cage. The produced MG powders and the in vivo test results on an 18 M-old Lanyu pig confirm the feasibility of the AM technique for producing implantable IMC-based prosthesis. Conclusion The non-crystalline structure of MGs alloy and the random crystalline composition of HEAs provide unique material properties that will substantially impact the development of future implantable prostheses.

Environmental indicators combined with risk analysis to evaluate potential wildfire incidence on the Dadu Plateau in Taiwan - Chao-Yuan Lin; Pei-Ying Shieh; Shao-Wei Wu; Po-Cheng Wang; Yung-Chau Chen (Natural Hazards, 2022)
Wildfire is a common disaster in the world, and it has a considerable impact on the safety of residents and ecological disturbance. Periodic wildfires are an urgent problem to be solved. This research uses big data from relevant departments to extract environmental indicators that affect wildfires, including satellite images, meteorological observations, and field surveys and establishes a risk model for the Spatio-temporal distribution of wildfires based on risk analysis. Previous studies using Differenced Normalized Burn Ratio (dNBR) to assess fire severity and distinguish wildfire ruins did not deal with the impact of atmospheric humidity on dNBR values. In this study, an adjustable fire threshold was developed to enable dNBR to improve the accuracy of identifying wildfire locations. Regarding the temporal distribution of wildfire risks, environmental vulnerability cannot specifically reflect the frequency of actual wildfires. If the hazard degree is introduced to calculate the wildfire risk, the coefficient of determination can be increased from 0.49 to 0.79. The verification of the village boundary zone depicts that the risk analysis can effectively show the temporal and spatial distribution of wildfire hotspots. On this basis, a village-level wildfire disaster prevention strategy can be formulated.

Investment Feasibility Analysis of Large Submersible Cage Culture in Taiwan: A Case Study of Snubnose Pompano (Trachinotus anak) and Cobia (Rachycentron canadum) - Hsun-Yu Lan; Farok Afero; Cheng-Ting Huang; Bo-Ying Chen; Po-Lin Huang; Yen-Lung Hou (Fishes, 2022)
Onshore farming for premium aquaculture is under scrutiny and criticism partially due to possible causes of adverse environmental impacts on other resource users and the surrounding environment. The best alternative to preventing or minimizing these impacts is to utilize open seawater by large submersible cage culture. The current operation in Taiwan has demonstrated that the culture operation is technically feasible but economically demanding because of high capital and operating costs. Therefore, this study conducted an economic analysis of the expansion of large submersible cage culture by selecting two premium species of snubnose pompano (Trachinotus anak) and cobia (Rachycentron canadum) and examined the profitability of large submersible cage culture investment. This study found that the current operation of four-unit cages highlighted a negative net present value and internal rate of return with a payback period of over ten and six years, respectively. Large submersible cage culture can be financially profitable when its operation unit expands from 8 to 24 units. Increasing unit cages to eight incurred a gross margin of 17.09%, BCR 1.21, with a payback period of 5.36 years. Expanding the operation to 24-unit cages was a potentially lucrative investment with a gross margin of 18.51%, BCR 1.23, PI 2.15, internal rate of return of 20.84%, and a payback period of 3.55 years. Sensitivity analyses revealed that market price and survival rate significantly impact the profitability of large submersible cage culture. Finally, it is suggested that producers could invest in 8-unit cages and maintaining the survival rate of snubnose pompano and cobia at 80% and 40%, respectively.

Bioeconomic evaluation of Eleutheronema tetradactylum farming: a case study in Taiwan - Cheng-Ting Huang; Farok Afero; Fang-Yu Lu; Bo-Ying Chen; Po-Lin Huang; Hsun-Yu Lan; Yen-Lung Hou (Fisheries Science, 2022)

miRNA–mRNA Integrative Analysis Reveals the Roles of miRNAs in Hypoxia-Altered Embryonic Development- and Sex Determination-Related Genes of Medaka Fish - Keng Po Lai; Nathan Yi Kan Tam; Yuelong Chen; Chi Tim Leung; Xiao Lin; Chau Fong Tsang; Yin Cheung Kwok; William Ka Fai Tse; Shuk Han Cheng; Ting Fung Chan; Richard Yuen Chong Kong (Frontiers in Marine Science, 2022)
Recent studies have shown hypoxia to be an endocrine disruptor that impairs sex differentiation and reproductive function, leading to male-biased F1 populations in fish. However, the molecular mechanisms through which hypoxia alters fish sex differentiation and therefore sex ratios remain poorly understood. In order to understand the potential role of miRNAs in mediating hypoxia-altered sex determination and differentiation in fish, we conducted small RNA sequencing and transcriptome sequencing on marine medaka ( Oryzias melastigma ) embryos that were exposed to hypoxia (2.0 ± 0.2 mg O 2 L – 1) for 40 h (encompassing a critical window of sex determination). We identified dysregulated miRNAs and mRNAs in the hypoxia-exposed embryo, and bioinformatic analysis of the integrative small RNA sequencing and transcriptome sequencing results revealed hypoxia to cause alterations of genes related to embryonic development through miRNA regulation. Importantly, we have identified miRNA-mRNA pairs that were reported to play roles in gonad development (novel miR-145-col9a3 and novel miRNA-94- arid5b), in sex hormone response (novel miRNA-210-ca2, novel miRNA-106-nr2f2, nbr-miR-29c-nr4a1, and ola-miR-92b-akr1d1), and in sex characteristic development (novel miRNA-145-mns1, nle-miR-20-sord, and ipu-miR-219b-abcc8). Our findings highlighted the possible roles of miRNA–mRNA in regulation of embryonic development and sex determination in response to hypoxic stress.

Intramyocardial injection of human adipose-derived stem cells ameliorates cognitive deficit by regulating oxidative stress–mediated hippocampal damage after myocardial infarction - Tsung-Ming LEE; Cheng-Che LEE; Horng-Jyh HARN; Tzyy-Wen Chiou; Ming-Hsi CHUANG; Chun-Hung CHEN; Chi-Hsuan CHUANG; Po-Cheng LIN; Shinn-Zong LIN (Journal of Molecular Medicine, 2021)
Cognitive impairment is a serious side effect of post-myocardial infarction (MI) course. We have recently demonstrated that human adipose-derived stem cells (hADSCs) ameliorated myocardial injury after MI by attenuating reactive oxygen species (ROS) levels. Here, we studied whether the beneficial effects of intramyocardial hADSC transplantation can extend to the brain and how they may attenuate cognitive dysfunction via modulating ROS after MI. After coronary ligation, male Wistar rats were randomized via an intramyocardial route to receive either vehicle, hADSC transplantation (1 × 10 6 cells), or the combination of hADSCs and 3-Morpholinosydnonimine (SIN-1, a peroxynitrite donor). Whether hADSCs migrated into the hippocampus was assessed by using human-specific primers in qPCR reactions. Passive avoidance test was used to assess cognitive performance. Postinfarction was associated with increased oxidative stress in the myocardium, circulation, and hippocampus. This was coupled with decreased numbers of dendritic spines as well as a significant downregulation of synaptic plasticity consisting of synaptophysin and PSD95. Step-through latency during passive avoidance test was impaired in vehicle-treated rats after MI. Intramyocardial hADSC injection exerted therapeutic benefits in improving cardiac function and cognitive impairment. None of hADSCs was detected in rat’s hippocampus at the 3rd day after intramyocardial injection. The beneficial effects of hADSCs on MI-induced histological and cognitive changes were abolished after adding SIN-1. MI-induced ROS attacked the hippocampus to induce neurodegeneration, resulting in cognitive deficit. The remotely intramyocardial administration of hADSCs has the capacity of improved synaptic neuroplasticity in the hippocampus mediated by ROS, not the cell engraftment, after MI. Key messages Human adipose-derived stem cells (hADSCs) ameliorated injury after myocardial infarction by attenuating reactive oxygen species (ROS) levels. Intramyocardial administration of hADSCs remotely exerted therapeutic benefits in improving cognitive impairment after myocardial infarction. The improved synaptic neuroplasticity in the hippocampus was mediated by hADSC-inhibiting ROS, not by the stem cell engraftment.

Electrical Impedance Tomography Analysis Between Two Similar Respiratory System Compliance During Decremetal PEEP Titration in ARDS Patients - Po-Lan Su; Wei-Chieh Lin; Yen-Fen Ko; Kuo-Sung Cheng; Chang-Wen Chen (Journal of Medical and Biological Engineering, 2021)
Purpose The positive end-expiratory pressure (PEEP) level with best respiratory system compliance (Crs) is frequently used for PEEP selection in acute respiratory distress syndrome (ARDS) patients. On occasion, two similar best Crs (where the difference between the Crs of two PEEP levels is < 1 ml/cm H 2 O) may be identified during decremental PEEP titration. Selecting PEEP under such conditions is challenging. The aim of this study was to provide supplementary rationale for PEEP selection by assessing the global and regional ventilation distributions between two PEEP levels in this situation. Methods Eight ARDS cases with similar best Crs at two different PEEP levels were analyzed using examination-specific electrical impedance tomography (EIT) measures and airway stress index (SIaw). Five Crs were measured at PEEP values of 25 cm H 2 O (PEEP 25 ), 20 cm H 2 O (PEEP 20 ), 15 cm H 2 O (PEEP H ), 11 cm H 2 O (PEEP I ), and 7 cm H 2 O (PEEP L ). The higher PEEP value of the two PEEPs with similar best Crs was designated as PEEP upper , while the lower designated as PEEP lower . Results PEEP H and PEEP I shared the best Crs in two cases, while similar Crs was found at PEEP I and PEEP L in the remaining six cases. SIaw was higher with PEEP upper as compared to PEEP lower (1.06 ± 0.10 versus 0.99 ± 0.09, p = 0.05). Proportion of lung hyperdistension was significantly higher with PEEP upper than PEEP lower (7.0 ± 5.1% versus 0.3 ± 0.5%, p = 0.0002). In contrast, proportion of recruitable lung collapse was higher with PEEP lower than PEEP upper (18.6 ± 4.4% versus 5.9 ± 3.7%, p < 0.0001). Cyclic alveolar collapse and reopening during tidal breathing was higher at PEEP lower than PEEP upper (34.4 ± 19.3% versus 16.0 ± 9.1%, p = 0.046). The intratidal gas distribution (ITV) index was also significantly higher at PEEP lower than PEEP upper (2.6 ± 1.3 versus 1.8 ± 0.7, p = 0.042). Conclusions PEEP upper is a rational selection in ARDS cases with two similar best Crs. EIT provides additional information for the selection of PEEP in such circumstances.

RSF1 requires CEBP/β and hSNF2H to promote IL-1β-mediated angiogenesis: the clinical and therapeutic relevance of RSF1 overexpression and amplification in myxofibrosarcomas - Chien-Feng Li; Ti-Chen Chan; Cheng-I. Wang; Fu-Min Fang; Po-Chun Lin; Shih-Chen Yu; Hsuan-Ying Huang (Angiogenesis, 2021)

Detection of Vestibular Schwannoma on Triple-parametric Magnetic Resonance Images Using Convolutional Neural Networks - Tzu-Hsuan Huang; Wei-Kai Lee; Chih-Chun Wu; Cheng-Chia Lee; Chia-Feng Lu; Huai-Che Yang; Chun-Yi Lin; Wen-Yuh Chung; Po-Shan Wang; Yen-Ling Chen; Hsiu-Mei Wu; Wan-You Guo; et al. (Journal of Medical and Biological Engineering, 2021)
Purpose The first step in typical treatment of vestibular schwannoma (VS) is to localize the tumor region, which is time-consuming and subjective because it relies on repeatedly reviewing different parametric magnetic resonance (MR) images. A reliable, automatic VS detection method can streamline the process. Methods A convolutional neural network architecture, namely YOLO-v2 with a residual network as a backbone, was used to detect VS tumors from MR images. To heighten performance, T1-weighted–contrast-enhanced, T2-weighted, and T1-weighted images were combined into triple-channel images for feature learning. The triple-channel images were cropped into three sizes to serve as input images of YOLO-v2. The VS detection effectiveness levels were evaluated for two backbone residual networks that downsampled the inputs by 16 and 32. Results The results demonstrated the VS detection capability of YOLO-v2 with a residual network as a backbone model. The average precision was 0.7953 for a model with 416 × 416-pixel input images and 16 instances of downsampling, when both the thresholds of confidence score and intersection-over-union were set to 0.5. In addition, under an appropriate threshold of confidence score, a high average precision, namely 0.8171, was attained by using a model with 448 × 448-pixel input images and 16 instances of downsampling. Conclusion We demonstrated successful VS tumor detection by using a YOLO-v2 with a residual network as a backbone model on resized triple-parametric MR images. The results indicated the influence of image size, downsampling strategy, and confidence score threshold on VS tumor detection.

Delayed association of acute particulate matter 2.5 air pollution exposure with loss of complexity in cardiac rhythm dynamics: insight from detrended fluctuation analysis - Tsung-Ying Tsai; Li-Wei Lo; Shin-Huei Liu; Wen-Han Cheng; Yu-Hui Chou; Wei-Lun Lin; Yenn-Jiang Lin; Shih-Lin Chang; Yu-Feng Hu; Fa-Po Chung; Jo-Nan Liao; Tze-Fan Chao; et al. (Environmental Science and Pollution Research, 2021)

Changes in arthropod community but not plant quality benefit a specialist herbivore on plants under reduced water availability - Po-An Lin; Chia-Ming Liu; Jia-Ang Ou; Cheng-Han Sun; Wen-Po Chuang; Chuan-Kai Ho; Natsuko Kinoshita; Gary W. Felton (Oecologia, 2021)

Matriptase and prostasin proteolytic activities are differentially regulated in normal and wounded skin - Shun-Cheng Chang; Chien-Ping Chiang; Chih-Hsin Lai; Po-Wen A. Du; Yu-Sin Hung; Yu-Hsuan Chen; Hui-Yu Yang; Hao-Yu Fang; Shiao-Pieng Lee; Hung-Jen Tang; Jehng-Kang Wang; Michael D. Johnson; et al. (Human Cell, 2020)

Hispidulin Inhibits Neuroinflammation in Lipopolysaccharide-Activated BV2 Microglia and Attenuates the Activation of Akt, NF-κB, and STAT3 Pathway - Chung-I Yu; Cheng-I Cheng; Ya-Fei Kang; Po-Chih Chang; In-Pin Lin; Yu-His Kuo; An-Jie Jhou; Mei-Ying Lin; Chung-Yi Chen; Chien-Hsing Lee (Neurotoxicity Research, 2020)

Potential Genes Related to Levofloxacin Resistance in Mycobacterium tuberculosis Based on Transcriptome and Methylome Overlap Analysis - Hai-cheng Li; Hui-xin Guo; Tao Chen; Wei Wang; Zhu-hua Wu; Liang Chen; Hui-zhong Wu; Gao-po Xu; Xun-xun Chen; Lin Zhou (Journal of Molecular Evolution, 2020)
Drug-resistant Mycobacterium tuberculosis ( M. tuberculosis ) has become an increasingly serious public health problem and has complicated tuberculosis (TB) treatment. Levofloxacin (LOF) is an ideal anti-tuberculosis drug in clinical applications. However, the detailed molecular mechanisms of LOF-resistant M. tuberculosis in TB treatment have not been revealed. Our study performed transcriptome and methylome sequencing to investigate the potential biological characteristics of LOF resistance in M. tuberculosis H37Rv. In the transcriptome analysis, 953 differentially expressed genes (DEGs) were identified; 514 and 439 DEGs were significantly downregulated and upregulated in the LOF-resistant group and control group, respectively. The KEGG pathway analysis revealed that 97 pathways were enriched in this study. In the methylome analysis, 239 differentially methylated genes (DMGs) were identified; 150 and 89 DMGs were hypomethylated and hypermethylated in the LOF-resistant group and control group, respectively. The KEGG pathway analysis revealed that 74 pathways were enriched in this study. The overlap study suggested that 25 genes were obtained. It was notable that nine genes expressed downregulated mRNA and upregulated methylated levels, including pgi , fadE4 , php , cyp132 , pckA , rpmB1 , pfkB , acg , and ctpF , especially cyp132 , pckA , and pfkB , which were vital in LOF-resistant M. tuberculosis H37Rv. The overlapping genes between transcriptome and methylome could be essential for studying the molecular mechanisms of LOF-resistant M. tuberculosis H37Rv. These results may provide informative evidence for TB treatment with LOF.

Conditional Overexpression of rtn4al in Muscle of Adult Zebrafish Displays Defects Similar to Human Amyotrophic Lateral Sclerosis - Cheng-Yung Lin; Po-Hsiang Zhang; You-Jei Chen; Chia-Lun Wu; Huai-Jen Tsai (Marine Biotechnology, 2019)

Engineering cyanobacteria for production of terpenoids - Po-Cheng Lin; Himadri B. Pakrasi (Planta, 2019)

Plasminogen/thrombomodulin signaling enhances VEGF expression to promote cutaneous wound healing - Tsung-Lin Cheng; Po-Ku Chen; Wei-Kai Huang; Cheng-Hsiang Kuo; Chia-Fong Cho; Kuan-Chieh Wang; Guey-Yueh Shi; Hua-Lin Wu; Chao-Han Lai (Journal of Molecular Medicine, 2018)

Characterization and adsorption capacity of potassium permanganate used to modify activated carbon filter media for indoor formaldehyde removal - Shih-Cheng Hu; Ying-Chen Chen; Xin-Zhi Lin; Angus Shiue; Po-Hua Huang; Yen-Che Chen; Shu-Mei Chang; Chao-Heng Tseng; Bin Zhou (Environmental Science and Pollution Research, 2018)

Extension of C. elegans lifespan using the ·NO-delivery dinitrosyl iron complexes - Hsiao-Wen Huang; Yen-Hung Lin; Min-Hsuan Lin; Ya-Rong Huang; Chih-Hung Chou; Hsiao-Chin Hong; Mei-Ren Wang; Yu-Ting Tseng; Po-Chun Liao; Min-Chuan Chung; Yu-Jie Ma; Shou-Cheng Wu; et al. (JBIC Journal of Biological Inorganic Chemistry, 2018)

Expression of serine peptidase inhibitor Kunitz type 1 in differentiated thyroid cancer - Chien-Liang Liu; Po-Sheng Yang; Ming-Nan Chien; Yuan-Ching Chang; Chi-Hsin Lin; Shih-Ping Cheng (Histochemistry and Cell Biology, 2018)

Cytoplasmic aryl hydrocarbon receptor regulates glycogen synthase kinase 3 beta, accelerates vimentin degradation, and suppresses epithelial–mesenchymal transition in non-small cell lung cancer cells - Ching-Hao Li; Chen-Wei Liu; Chi-Hao Tsai; Yi-Jen Peng; Yu-Hsuan Yang; Po-Lin Liao; Chen-Chen Lee; Yu-Wen Cheng; Jaw-Jou Kang (Archives of Toxicology, 2017)

Anti-apoptotic and Pro-survival Effects of Food Restriction on High-Fat Diet-Induced Obese Hearts - Yi-Yuan Lin; Po-Shiuan Hsieh; Yu-Jung Cheng; Shiu-Min Cheng; Chiao-nan Chen; Chih-Yang Huang; Chia-Hua Kuo; Chung-Lan Kao; Woei-Cherng Shyu; Shin-Da Lee (Cardiovascular Toxicology, 2017)

Development of a fluorescence resonance energy transfer–based intracellular assay to identify novel enterovirus 71 antivirals - Wen-Wen Lu; Fang-Yen Kung; Po-An Deng; Yu-Chu Lin; Cheng-Wen Lin; Szu-Hao Kung (Archives of Virology, 2017)

Curcumin downregulates p38 MAPK-dependent X-ray repair cross-complement group 1 (XRCC1) expression to enhance cisplatin-induced cytotoxicity in human lung cancer cells - Chun-Liang Tung; Yi-Jun Jian; Jyh-Cheng Chen; Tai-Jing Wang; Wen-Ching Chen; Hao-Yu Zheng; Po-Yuan Chang; Kai-Sheng Liao; Yun-Wei Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Sulbactam treatment for pneumonia involving multidrug-resistant Acinetobacter calcoaceticus–Acinetobacter baumannii complex - Huang-Shen Lin; Ming-Hsun Lee; Chun-Wen Cheng; Po-Chang Hsu; Hsieh-Shong Leu; Ching-Tai Huang; Jung-Jr Ye (Infectious Diseases, 2015)

Rapid detection of copper chlorophyll in vegetable oils based on surface-enhanced Raman spectroscopy - Wei-Nan Lian; Jessie Shiue; Huai-Hsien Wang; Wei-Chen Hong; Po-Han Shih; Chao-Kai Hsu; Ching-Yi Huang; Cheng-Rong Hsing; Ching-Ming Wei; Juen-Kai Wang; Yuh-Lin Wang (Food Additives & Contaminants: Part A, 2015)

The Association of RAB18 Gene Polymorphism (rs3765133) with Cerebellar Volume in Healthy Adults - Chih-Ya Cheng; Albert C. Yang; Chu-Chung Huang; Mu-En Liu; Ying-Jay Liou; Jaw-Ching Wu; Shih-Jen Tsai; Ching-Po Lin; Chen-Jee Hong (The Cerebellum, 2014)

Minocycline accelerates hypoxia-inducible factor-1 alpha degradation and inhibits hypoxia-induced neovasculogenesis through prolyl hydroxylase, von Hippel–Lindau-dependent pathway - Ching-Hao Li; Po-Lin Liao; Ya-Ting Yang; Shih-Hsuan Huang; Cheng-Hui Lin; Yu-Wen Cheng; Jaw-Jou Kang (Archives of Toxicology, 2013)

Glycogen synthase kinase-3β inactivation is an intracellular marker and regulator for endotoxemic neutrophilia - Tsan-Tzu Yang; Chia-Ling Chen; Wei-Chieh Lin; Yee-Shin Lin; Po-Chun Tseng; Chia-Yuan Hsieh; Yu-Hong Chen; Wei-Ching Huang; Cheng-Chieh Tsai; Chi-Yun Wang; Chi-Chang Shieh; Chiou-Feng Lin (Journal of Molecular Medicine, 2013)

Comparison of MODIS land surface temperature and ground-based observed air temperature in complex topography - Yen-Jen Lai; Ching-Feng Li; Po-Hsiung Lin; Tsong-Hue Wey; Cheng-Sheng Chang (International Journal of Remote Sensing, 2012)

Niacin improves ischemia-induced neovascularization in diabetic mice by enhancement of endothelial progenitor cell functions independent of changes in plasma lipids - Po-Hsun Huang; Chih-Pei Lin; Chao-Hung Wang; Chia-Hung Chiang; Hsiao-Ya Tsai; Jia-Shiong Chen; Feng-Yen Lin; Hsin-Bang Leu; Tao-Cheng Wu; Jaw-Wen Chen; Shing-Jong Lin (Angiogenesis, 2012)

Occurrence of diarrheagenic Escherichia coli genes in raw water of water treatment plants - Shih-Wei Huang; Bing-Mu Hsu; Yen-Jui Su; Dar-Der Ji; Wei-Chen Lin; Jyh-Larng Chen; Feng-Cheng Shih; Po-Min Kao; Yi-Chou Chiu (Environmental Science and Pollution Research, 2012)

Oxidative stress in greater duckweed (Spirodela polyrhiza) caused by long-term NaCl exposure - In-Hwa Chang; Kai-Teng Cheng; Po-Chuan Huang; Yen-Yu Lin; Lee-Ju Cheng; Tai-Sheng Cheng (Acta Physiologiae Plantarum, 2012)

Evaluation of the optimal strategy for ex situ bioremediation of diesel oil-contaminated soil - Ta-Chen Lin; Po-Tsen Pan; Chiu-Chung Young; Jo-Shu Chang; Tsung-Chung Chang; Sheng-Shung Cheng (Environmental Science and Pollution Research, 2011)

Secular trend of genome types of respiratory adenovirus type 3 during 1983–2005: a study from Taiwan - Yung-Cheng Lin; Kuei-Hsiang Lin; Guan-Ming Ke; Min-Sheng Lee; Pei-Chin Lin; Hsin-Fu Liu; Li-Ching Hsu; Po-Liang Lu (Archives of Virology, 2010)

Elucidation of susceptible factors to endoplasmic reticulum stress-mediated anticancer activity in human hepatocellular carcinoma - Po-Cheng Chiang; Jui-Ling Hsu; Ting-Chun Yeh; Shiow-Lin Pan; Jih-Hwa Guh (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

Prevention of TGF-β-induced apoptosis by interlukin-4 through Akt activation and p70S6K survival signaling pathways - Sue-Jane Lin; Chungming Chang; Ah-Kau Ng; Shu-Han Wang; Jia-Je Li; Cheng-po Hu (Apoptosis, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Atmosphic pollutants study of particles ionic species during high wind speed (>7 m s-1) near Taiwan strait in central Taiwan from 2004 to 2005 - Guor-Cheng Fang; Yuh-Shen Wu; Wen-Jhy Lee; Chi-Kwong Lin; Chung-Po Lin (Environmental Monitoring and Assessment, 2007)